2021
DOI: 10.15537/smj.2021.2.25686
|View full text |Cite
|
Sign up to set email alerts
|

Safety and cost-effectiveness of outpatient thyroidectomy

Abstract: To investigate the safety and cost-effectiveness of outpatient thyroidectomy and provide a systematic postoperative protocol for safe discharge. Methods: In this retrospective review, the medical records of all patients who underwent total, hemi, or completion thyroidectomy from July 2017 to April 2019 at 2 tertiary care hospitals were reviewed. Multivariable analysis was performed on the potential predictors of postoperative complications. Healthcare costs were calculated by the type of admission based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…On the other hand, Al-Qahtani et al in Tabuk reported an overall prevalence of 72.3%, 12 while Al-Hakami et al from Jeddah reported a complication rate of 43.45%, 13 and Qobty et al from Aseer region reported a rate as high as 91%. 14 Relatively moderate rates were reported by Al-Eissa et al from Riyadh (14.8%), 15 Al-Amri from Dammam (17.4%) 16 and Al-Shareef et al from Makkah region (16%). 17 In most studies, hypocalcemia is the commonest complication encountered following thyroidectomy.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…On the other hand, Al-Qahtani et al in Tabuk reported an overall prevalence of 72.3%, 12 while Al-Hakami et al from Jeddah reported a complication rate of 43.45%, 13 and Qobty et al from Aseer region reported a rate as high as 91%. 14 Relatively moderate rates were reported by Al-Eissa et al from Riyadh (14.8%), 15 Al-Amri from Dammam (17.4%) 16 and Al-Shareef et al from Makkah region (16%). 17 In most studies, hypocalcemia is the commonest complication encountered following thyroidectomy.…”
Section: Discussionmentioning
confidence: 91%
“…Table 5 shows the various complications recorded in different centers across Saudi Arabia. [11][12][13][14][15][16][17] Al-Harbi and Ahmed reported an overall prevalence of 9.6% among 310 patients who underwent thyroidectomy. 11 However, this was a retrospective study and only three major complication types were deliberately recorded.…”
Section: Discussionmentioning
confidence: 99%
“…The included studies [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] comprised of 46,866 patients divided into 37,814 inpatients and 9025 outpatients. Study characteristics and data from each of these studies are presented in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The paper of AlEssa et al 1 is concerning a debated issue since several years: can same day thyroidectomy be performed safely? Although the number of reported patients is relatively low, the outcome between outpatients and inpatients was not different in the experience of the authors, being in line with previous studies, 2 provided a high-volume surgeon as in this report, is available.…”
Section: To the Editormentioning
confidence: 99%
“…We thank Dr. Sandro Contini for his interest and invaluable comment on our study, “Safety and cost-effectiveness of outpatient thyroidectomy A retrospective observational study.” 1 …”
Section: Reply From the Authormentioning
confidence: 99%